2006
DOI: 10.1002/mrd.20611
|View full text |Cite
|
Sign up to set email alerts
|

Decreased protein tyrosine phosphorylation and membrane fluidity in spermatozoa from infertile men with varicocele

Abstract: Varicocele is a prevalent pathology among infertile men. The mechanisms linking this condition to infertility, however, are poorly understood. Our previous work showed a relationship between sperm functional quality and the ability of spermatozoa to respond to capacitating conditions with increased membrane fluidity and protein tyrosine phosphorylation. Given the reported association between varicocele, oxidative stress, and sperm dysfunction, we hypothesized that spermatozoa from infertile patients with varic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…This result may probably be due to the reduced expression of AR determining a decreased responsiveness to DHT. Besides, our data are in agreement with the idea that grade II/III infertile varicocele presents an alteration in sperm plasma membrane dynamics due a decreased cholesterol mobility (Buffone et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This result may probably be due to the reduced expression of AR determining a decreased responsiveness to DHT. Besides, our data are in agreement with the idea that grade II/III infertile varicocele presents an alteration in sperm plasma membrane dynamics due a decreased cholesterol mobility (Buffone et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This deficiency was associated with an impairment in protein tyrosine phosphorylation and an incapacity to develop hyperactivation. An association between inability to increase membrane fluidity during capacitation and tyrosine phosphorylation and functional deficiencies was also observed in pathologic semen samples of patients with asthenozoospermia and varicocele (Buffone et al, 2005; Buffone et al, 2006). Thus, a common theme connecting defects in membrane dynamics and sperm functional quality is evident.…”
Section: Discussionmentioning
confidence: 82%
“…Immunofluorescence was employed to examine the incidence of tyrosine phosphorylated sperm cells. L90 cells from normozoospermic individuals were incubated for 6 h under capacitating conditions and the percentage of cells showing fluorescence in their tails was measured as previously described (Buffone et al. , 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In this regards, previous investigations suggested that these cells have membrane fluidity alterations (Ambrosini et al. , 2001, 2003; Buffone et al. , 2005, 2006).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation